Evolutionary design of combinational circuits using fractional-order fitness functions - Reis, Cecília (2019)
This paper analyses the performance of a genetic algorithm using the new concept of fractional-order dynamic fitness function, for the synthesis of combinational logic circuits. The experiments reveal superior results in terms of speed and convergence to achieve a solution.